2009
DOI: 10.1016/j.jacc.2008.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Lone Atrial Fibrillation by the Angiotensin-II Converting Enzyme Inhibitor Ramipril in Normotensive Patients

Abstract: Ramipril is effective in preventing relapses of LAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 40 publications
0
66
0
5
Order By: Relevance
“…6,8,[16][17][18][19] On the other hand, a suppressive effect of RASIs on AF recurrences after PVI was demonstrated in patients with a relatively small LA. 15,20 The present study showed that the use of RASIs was closely associated with the AF recurrence-free rates in the patients with a non-dilated LA, but not at all in the patients with a dilated LA. It has been reported that LA dilatation correlates with the degree of 22 and both atrial dilation and fibrosis are only partially reversible after sinus rhythm is restored, 23,24 whereas short-term electrical remodelling is completely reversible.…”
Section: La Size and Fibrosismentioning
confidence: 48%
See 1 more Smart Citation
“…6,8,[16][17][18][19] On the other hand, a suppressive effect of RASIs on AF recurrences after PVI was demonstrated in patients with a relatively small LA. 15,20 The present study showed that the use of RASIs was closely associated with the AF recurrence-free rates in the patients with a non-dilated LA, but not at all in the patients with a dilated LA. It has been reported that LA dilatation correlates with the degree of 22 and both atrial dilation and fibrosis are only partially reversible after sinus rhythm is restored, 23,24 whereas short-term electrical remodelling is completely reversible.…”
Section: La Size and Fibrosismentioning
confidence: 48%
“…A small randomized study with ACEIs (ramipril) demonstrated a preventive effect on AF recurrences and LA remodelling, 15 whereas three recent prospective randomized studies did not. [6][7][8] Therefore, it has been increasingly recognized that RASIs alone cannot suppress AF in humans.…”
Section: Effect Of Rasis On Af Recurrences As Compared With Previous mentioning
confidence: 99%
“…Furthermore, a recent report on the ON-TARGET study 4 indicated that 80 mg of telmisartan daily was equivalent to the ACE inhibitor ramipril, and was effective in preventing relapses of lone AF. 8 Further, with a dose of 10 mg daily, not only did it have an antihypertensive action but it also prevented atrial fibrillation. It is not Figure 1: Changes in the blood pressure (Left, A) and heart rate (Right, B) at baseline, during treatment with 40 mg (Low-dose group) and 80 mg (High-dose group) of telmisartan.…”
Section: Discussionmentioning
confidence: 98%
“…7 Previous meta-analyses based on several post hoc analyses of randomized controlled trials have shown that RAS blockers significantly reduced the risk of new-onset AF ranging from 28% to 49%, but this benefit was limited to patients with systolic left ventricular dysfunction or hypertension with LVH. 10,11 For secondary prevention of AF, several relatively small prospective randomized studies [12][13][14] have demonstrated that therapies with ACEI/ARBs conferred an additional benefit on risk of recurrent AF in these patients when coadministered with antiarrhythmic drug therapy, usually amiodarone, compared with antiarrhythmic drug alone. Whether RAS blockade could prevent recurrent AF in paroxysmal AF patients with minor underlying cardiac pathology, who are not undergoing cardioversion and do not receive antiarrhythmic drugs therapy or ACEIs, remains controversial.…”
Section: Main Findingsmentioning
confidence: 99%